Penyakit Mosaik pada Koro Pedang - Tri Asmira Damayanti (Jurnal Fitopatologi Indonesia, 2015)
Recently, a mosaic disease was observed on jack bean cultivation in Dramaga, Bogor,West Java. The symptom on infected plants, i.e. combination of pale and dark green area was more obvious on young leaves. Vein banding, leaf malformation, and growth inhibition was also observed in infected plants. The symptom was not very obvious in older leaves. Serological detection gave positive reaction to Bean common mosaic virus (BCMV) antiserum, but reaction was negative when detected using specific primer to coat protein (CP) of BCMV strain black eye by reverse transcription polymerase chain reaction. DNA fragments were successfully amplified by RT-PCR using universal primer of CP gene and degenerated primer for cylindrical inclusion gen (CI) of Potyvirus. DNA analysis showed the highest homology (86.4–91.5%) to several isolates of BCMV-infecting different crops from several countries based on partial sequence of CP, whereas based on partial sequence of CI the highest homology (87.3%) was to BCMV-RU1-P. This is the first report of BCMV infection on jack bean in Bogor, West Java, Indonesia.